2022
DOI: 10.1155/2022/6566144
|View full text |Cite
|
Sign up to set email alerts
|

Innovation of Digital Multimedia VR Technology in Music Education Curriculum in Colleges and Universities

Abstract: The art of music is the art of hearing, helping humans to establish good aesthetic interests. Music education is not only an important means of quality education for students, but also an important way to cultivate musical talents in colleges and universities. It inspires students’ lofty ideals, cultivates their sentiments, and improves their aesthetic ability and cultural quality. The emergence of digital multimedia VR technology has made the traditional music education in colleges and universities seem a bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The study reported a correlation between the execution of such courses and various influencing factors. Despite progress in digital multimedia, VR-enabled teaching has shortcomings, such as insufficient art digital multimedia curriculum focusing on VR, limitations of contemporary requirements in the course, gaps between implementation and the developmental stages of teaching methods, and limited teacher proficiency in digital multimedia using VR [68]. A similar study assessed students' experience with VR tool and their comprehension of 3D vectors in a university physics course.…”
Section: Behavioralmentioning
confidence: 99%
“…The study reported a correlation between the execution of such courses and various influencing factors. Despite progress in digital multimedia, VR-enabled teaching has shortcomings, such as insufficient art digital multimedia curriculum focusing on VR, limitations of contemporary requirements in the course, gaps between implementation and the developmental stages of teaching methods, and limited teacher proficiency in digital multimedia using VR [68]. A similar study assessed students' experience with VR tool and their comprehension of 3D vectors in a university physics course.…”
Section: Behavioralmentioning
confidence: 99%
“…In [37], the authors explored innovations in music curricula in colleges and universities in the era of digital multimedia VR technology. The survey on the current situation of the implementation of digital multimedia VR teaching in colleges provided a more detailed basis for the reform of the music curriculum.…”
Section: From a Student's Experience Point Of Viewmentioning
confidence: 99%
“…[2,4,5,8,11,[13][14][15][16][17][18][19][20][22][23][24]27,29,[33][34][35][36][37],39-52,58-69,71-79,82-91,93-101,103,104,106-128] [53,92,129,130] [28,54-56,79]…”
mentioning
confidence: 99%
“…Other researchers have explored the use of VR in various aspects of music education, including curriculum innovation, social virtual reality robots, pitch perception training, and vocal training. Xiao, [12] found that 72.2% of students considered the implementation of digital multimedia VR art courses to be effective. Shahab [13] observed a general upward trend in the musical ability of children with high-functioning autism when utilising social virtual reality robots for music education.…”
Section: Introductionmentioning
confidence: 99%